SIFAT ORGANOLEPTIK DAN NILAI TAMBAH YOGURT BEKU DENGAN PENAMBAHAN EKSTRAK KULIT BUAH NAGA MERAH (Hyloceneus polyrhizus) [Organoleptics Properties and Value Added of Frozen Yoghurt with Addition of Red Dragon Fruit Skin Extracts (Hylocereus polyrhizus)] - Analianasari Analianasari; Marlinada Apriyani (Jurnal Teknologi & Industri Hasil Pertanian, 2019)
Frozen yoghurt is a frozen food product fermented milk by Streptococcus thermophillus bacteria and Lactobacillus bulgaricus which contain protein, vitamins, minerals, and low fat. This study aimed to determine the organoleptic of frozen yoghurt enriched with red dragon fruit skin extract. The design of the study used a completely randomized design (RAL) with a single treatment, namely red dragon fruit skin extract consisting of 4 concentration levels: 0% , 25%, 30%, and 45%. Each of which was added to the amount of cow's milk media as raw material for frozen yogurt. The best treatment obtained in terms of texture, color, taste, aroma and overall acceptance were the addition of 25% dragon fruit skin extract. This yoghurt had criteria of slightly soft texture, pink color, yoghurt flavor, and sour taste.